2017
DOI: 10.1371/journal.pone.0176515
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study: Determination of potential risk factors for the colonization of healthy volunteers with Streptococcus gallolyticus subsp. gallolyticus

Abstract: Streptococcus gallolyticus subsp. gallolyticus was identified in humans and animals as commensal of the gut and can act as a causative agent of endocarditis and septicemia. A case-control study was performed to identify yet unknown risk factors for the transmission of this facultative pathogen. The prevalence in the gut of 99 healthy volunteers was determined using real-time polymerase chain reaction resulting in 62.5% S. gallolyticus subsp. gallolyticus positive excrements. Subsequent cultivation offered thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
1
16
1
Order By: Relevance
“…Whether SGG plays an etiological role precipitating the occurrence of polyps and tumors or acquires a strong colonization property in response to a favorable ecological environment created by the tumor itself or preexisting conditions remains unknown. It is worth mentioning that, even though asymptomatic carriage of SGG is estimated to be between 5% and 15% in the literature, mostly using enrichment on selective media and culture techniques, a recent study indicated a much higher carriage rate (∼60%) by using quantitative realtime PCR (28).…”
Section: Discussionmentioning
confidence: 99%
“…Whether SGG plays an etiological role precipitating the occurrence of polyps and tumors or acquires a strong colonization property in response to a favorable ecological environment created by the tumor itself or preexisting conditions remains unknown. It is worth mentioning that, even though asymptomatic carriage of SGG is estimated to be between 5% and 15% in the literature, mostly using enrichment on selective media and culture techniques, a recent study indicated a much higher carriage rate (∼60%) by using quantitative realtime PCR (28).…”
Section: Discussionmentioning
confidence: 99%
“…The counts ≥ 10 8 cfu were found in the Livanjski cheeses after salting (S2, S4). Streptococcus gallolyticus is known as part of the microbiota in artisan raw milk cheeses (Pacini et al ; Gaglio et al ) but is also noted as a facultative human pathogen (Dumke et al ). The occurrence of Str.…”
Section: Discussionmentioning
confidence: 99%
“…The fecal carriage rate of SBSEC member in humans is varying from five to over 60% (Table 1 ) (Klein et al, 1977 ; Noble, 1978 ; Potter et al, 1998 ; Abdulamir et al, 2010 ; Al-Jashamy et al, 2010 ; Chirouze et al, 2013 ; Lopes et al, 2014 ; Boltin et al, 2015 ; Dumke et al, 2017 ; Kaindi et al, 2017 ). This variation might depend on detection techniques and regional differences.…”
Section: Prevalence and Colonization Of Sbsec In Animals And Humansmentioning
confidence: 99%
“…Furthermore, most studies were conducted using a hospital-derived population with possible differences in age, sex and underlying diseases that limits extrapolation to the general population. (Huang et al, 2008 ; Chirouze et al, 2013 ; Lopes et al, 2014 ; Dumke et al, 2017 ; Harris et al, 2017 ). Oral niche colonization in humans seems to be infrequent, but isolation of SII, SGP , and SE was confirmed from dental plaques and root caries lesions (Sissons et al, 1988 ; Shen et al, 2005 ; Arul and Palanivelu, 2014 ).…”
Section: Prevalence and Colonization Of Sbsec In Animals And Humansmentioning
confidence: 99%